The contribution of Spartina Maratima (Curtis) Fernald to the primary production of the Swartkops estuary - Pierce, Shirley May (Rhodes University, Faculty of Science, Botany Department, 1979)
The primary production of Spartina maritima, the dominant macrophyte of the intertidal salt marshes of the Swartkops estuary, was determined for inclusion into the proposed ecosystem model. Several methods for measuring net production devised for North temperate Spartina species were used, as no single method was considered reliable for the local species. In addition, a new method was devised to take into account the aseasonal growth behaviour of S. maritima . Most energy for growth appears to be directed into leaf production, rather than shoot growth. Live net production values were 523-680 g mâ »Â²Â‚ yr â »Â¹, which are generally lower than estimates of N. American Spartina species. Total Live production of S. maritima for the whole Swartkops estuary was 495,6 x I0Â³kg yr â »Â¹, which is an estimation of potential food resources. Formation of S. maritima detritus by decomposition was significantly related to air and water temperatures. Thus detritus production showed a wide seasonal variation about a mean of 374 g mâ »Â² yrâ »Â¹. The total S. maritima detritus production of 307,5 x I0Â³kg for the whole Swartkops estuary was determined as an estimate of available food resources. Export of detrital material from Spartina marshes to estuarine waters was negligible. Even during a maximal Equinoctial tide, only 6,26 dry g mâ »Â² detritus was exported from the creek catchment area of Spartina stands. This study has shown that concepts evolved for North temperate estuaries should be carefully considered before being applied to local situations, particularly in view of the relatively low, aseasonal production of S. maritima and the negligible contribution of its detritus to estuarine waters. Furthermore, it is essential that utilisation of primary production by secondary producers be determined before the function of the estuarine ecosystem may be understood
Keywords: Estuarine biology -- South Africa -- Swartkops River Estuary; Spartina